Leadership During the Boston Marathon Bombings: A Qualitative After-Action Review. (22nd June 2015) - Goralnick, Eric; Halpern, Pinchas; Loo, Stephanie; Gates, Jonathan; Biddinger, Paul; Fisher, John; Velmahos, George; Chung, Sarita; Mooney, David; Brown, Calvin; Barnewolt, Brien; Burke, Peter; et al.
Abstract: Objective: On April 15, 2013, two improvised explosive devices (IEDs) exploded at the Boston Marathon and 264 patients were treated at 26 hospitals in the aftermath. Despite the extent of injuries sustained by victims, there was no subsequent mortality for those treated in hospitals. Leadership decisions and actions in major trauma centers were a critical factor in this response. Methods: The objective of this investigation was to describe and characterize organizational dynamics and leadership themes immediately after the bombings by utilizing a novel structured sequential qualitative approach consisting of a focus group followed by subsequent detailed interviews and combined expert analysis. Results: Across physician leaders representing 7 hospitals, several leadership and management themes emerged from our analysis: communications and volunteer surges, flexibility, the challenge of technology, and command versus collaboration. Conclusions: Disasters provide a distinctive context in which to study the robustness and resilience of response systems. Therefore, in the aftermath of a large-scale crisis, every effort should be invested in forming a coalition and collecting critical lessons so they can be shared and incorporated into best practices and preparations. Novel communication strategies, flexible leadership structures, and improved information systems will be necessary to reduce morbidity and mortality during future events. ( Disaster Med Public Health Preparedness . 2015;9:489–495)